Minireview: Chromatin-based regulation of iron homeostasis in plants - Su, Justin; Yao, Zhujun; Wu, Yixuan; Lee, Joohyun; Jeong, Jeeyon (Frontiers in Plant Science, 2022)
Plants have evolved delicate mechanisms to effectively respond to changes in the availability of nutrients such as iron. The responses to iron status involve controlling gene expression at multiple levels. The regulation of iron deficiency response by a network of transcriptional regulators has been extensively studied and recent research has shed light on post-translational control of iron homeostasis. Although not as considerably investigated, an increasing number of studies suggest that histone modification and DNA methylation play critical roles during iron deficiency and contribute to fine-tuning iron homeostasis in plants. This review will focus on the current understanding of chromatin-based regulation on iron homeostasis in plants highlighting recent studies in Arabidopsis and rice. Understanding iron homeostasis in plants is vital, as it is not only relevant to fundamental biological questions, but also to agriculture, biofortification, and human health. Ultimately, a comprehensive overview of the effect and mechanism of chromatin-based regulation in response to iron status will provide critical insights in elucidating the complexities of iron homeostasis and contribute to improving iron nutrition in plants.